THE INFLUENCE OF OWNERSHIP STRUCTURE ON AUDIT FEE - Yudhistira Dwica Anandya; Andrian Budi Prasetyo (Riset Akuntansi Keuangan, 2019)
The aim of the research was to analyze the effect of managerial ownership, foreign ownership, government ownership, ownership concentration, and percentage of shares of multiple large shareholders on audit fees. The independent variables were managerial ownership, foreign ownership, government ownership, ownership concentration, and percentage of shares of multiple large shareholders; while, the independent variable was audit fees. All non-financial companies listed in the Indonesia Stock Exchange in 2013-2015 were sampled. Proportionate stratified random sampling was applied to 207 sampled companies verified using slovin formula and multiple regression analysis to test the hypothesis of the research. This research found that the managerial ownership and the percentage of multiple large shareholders were negatively affected audit fees. Moreover, government ownership positively and significantly influenced audit fee; while, foreign ownership and ownership concentration had no significant effect on audit fee.